2022
DOI: 10.1002/jmcd.12273
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of professional identity development and experiences of cultural insensitivity among international counselor education doctoral students

Abstract: The authors used a qualitative research method to examine experiences of cultural insensitivity and their influences on professional identity among 13 international counselor education students. Participants described experiencing discrimination and how these experiences pushed them to incorporate advocacy into their professional identities. Participants also described the impact of discrimination on their cultural identities and the lack of global perspectives in mental health professions. Implications for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The highlights, "few women in elected political positions, fathers deal with facts, mothers with feelings" (Hofstede, 2011, p. 12), resemble the incident in this study's context where the international students did not accept a female leader. Furthermore, the incidents mentioned by T1 and T2 about students' othering Kurdish people or a students' shouting hatred towards Palestine and the girl coming there resemble the incident in Kuo et al (2022) where a student was approached as if he was a representative of the entire Muslim community and the one responsible from the 9/11 incident. In order to be able to eliminate these conflicts, cultural awareness and sensitivity levels of both students and instructors should be raised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highlights, "few women in elected political positions, fathers deal with facts, mothers with feelings" (Hofstede, 2011, p. 12), resemble the incident in this study's context where the international students did not accept a female leader. Furthermore, the incidents mentioned by T1 and T2 about students' othering Kurdish people or a students' shouting hatred towards Palestine and the girl coming there resemble the incident in Kuo et al (2022) where a student was approached as if he was a representative of the entire Muslim community and the one responsible from the 9/11 incident. In order to be able to eliminate these conflicts, cultural awareness and sensitivity levels of both students and instructors should be raised.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ferdinand-James (2015) highlighted that minority and international students often perceived and reported cultural insensitivity in the classroom. Similarly, Kuo et al (2022) reported that international students experienced cultural insensitivity, which led to discrimination and negative impacts on their identities. There are other factors that can contribute to conflicts related to the absence of cultural sensitivity, such as English Language Teaching (ELT) coursebooks presenting a different culture to EFL learners.…”
Section: Introductionmentioning
confidence: 99%